Final Results of a Phase I Trial of WST-11 (TOOKAD Soluble) Vascular-targeted Photodynamic Therapy for Upper Tract Urothelial Carcinoma. Issue 5 (1st May 2023) - Yip, Wesley; Sjoberg, Daniel D.; Nogueira, Lucas M.; Tracey, Andrew T.; Alvim, Ricardo G.; Reisz, Peter A.; Demac, Quinlan; Benfante, Nicole E.; Vanden Berg, Rand W.; Kim, Kwanghee; Al-Ahmadie, Hikmat; Lin, Oscar; et al.
Abstract : Purpose: Vascular-targeted photodynamic therapy with the intravascular photosensitizing agent padeliporfin (WST-11/TOOKAD-Soluble) has demonstrated therapeutic efficacy as an ablative treatment for localized cancer with potential adaptation for endoscopic management of upper tract urothelial carcinoma. This Phase I trial (NCT03617003) evaluated the safety of vascular-targeted photodynamic therapy with WST-11 in upper tract urothelial carcinoma. Materials and Methods: Nineteen patients underwent up to 2 endoscopic vascular-targeted photodynamic therapy treatments, with follow-up for up to 6 months. Patients who had residual or recurrent upper tract urothelial carcinoma (any grade/size) failing prior endoscopic treatment or unable or unwilling to undergo surgical resection were eligible for inclusion. The primary endpoint was to identify the maximally tolerated dose of laser light fluence. A dose escalation model was employed, with increasing light fluence (100-200 mW/cm) using a modified continual reassessment method. The secondary endpoint was treatment efficacy, defined by absence of visible tumor and negative urine cytology 30 days posttreatment. Results: Fourteen (74%) patients received the maximally tolerated dose of 200 mW/cm, 2 (11%) of whom experienced a dose-limiting toxicity. The initial 30-day treatment response rate was 94% (50% complete, 44% partial). Eight patients underwent a second treatment, with a final observed 68% complete response rate. Leading toxicities were flank pain (79%) and hematuria (84%), which were transient. No ureteral strictures associated with treatment were identified during follow-up. Conclusions: Vascular-targeted photodynamic therapy with WST-11 has an acceptable safety profile with strong potential as an effective, kidney-sparing endoscopic management option for upper tract urothelial carcinoma. The recently initiated multicenter Phase 3 ENLIGHTED trial (NCT04620239) is expected to provide further evidence on this therapy.